Shear strength of compacted soil under infiltration condition - Rahardjo, Harianto (2011)
Landslides in residual soil slopes are commonly induced by rainfall infiltration. These residual soils are typically in an unsaturated state with negative pore-water pressures or matric suctions since the groundwater tables in steep slopes are often deep. The net normal and shear stresses of the soil remain essentially constant during rainwater infiltration into the slope. Failure of the slope during rainfall can be primarily associated with the decrease in the matric suction of the soil. The objective of the study was to investigate the strength and deformation characteristics of a residual soil of the Bukit Timah Granitic Formation during infiltration that leads to slope failure. There were two modified direct shear apparatuses used. One apparatus was used for the determination of shear strength under controlled suction conditions while the other apparatus was used for shearing-infiltration tests. The shearing-infiltration test results were compared with the shear strength values obtained from the shearing tests under constant suction. The shearing-infiltration test results indicate a close relationship between the decreasing matric suction and the increasing displacement rate of the soil specimen. At the initial part of the infiltration process, there is a rapid reduction in matric suction that is accompanied by little movement in the soil. When failure of the soil is imminent, the soil movement will accelerate.